2020
DOI: 10.1002/jctb.6623
|View full text |Cite
|
Sign up to set email alerts
|

23 central composite rotatable design for the production of neem oil nanoemulsion for antifungal and antiparasitic applications

Abstract: BACKGROUND: The present study describes the design and production of an oil-in-water nanoemulsion composed of neem oil as the inner phase for use as an antifungal and antiparasitic control in aquaculture. A 2 3 central composite rotatable design adopting surface response was used as the experimental design, setting the neem oil concentration (4-15%), surfactant concentration (0.5-10%) and sonication power (20-90%) as the independent variables, while the droplet size, polydispersity index (PDI) and zeta potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…For example, Rabelo et al demonstrated the preparation of a nanoemulsion for encapsulating a fungicide (neem oil) as a new antifungal and antiparasitic control measure in aquaculture. 5 The optimal formulation of a nanoemulsion was found to have 9% of neem oil and 5.25% of polysorbate 20. At a concentration of 200 mg L −1 of this nanoemulsion, a 100% parasitic mortality against Saprolegnia parasitica was observed.…”
Section: In Focus: Latest Development Of Nanotechnology In Latin Americamentioning
confidence: 99%
“…For example, Rabelo et al demonstrated the preparation of a nanoemulsion for encapsulating a fungicide (neem oil) as a new antifungal and antiparasitic control measure in aquaculture. 5 The optimal formulation of a nanoemulsion was found to have 9% of neem oil and 5.25% of polysorbate 20. At a concentration of 200 mg L −1 of this nanoemulsion, a 100% parasitic mortality against Saprolegnia parasitica was observed.…”
Section: In Focus: Latest Development Of Nanotechnology In Latin Americamentioning
confidence: 99%